Metagenomic analysis reveals unusually high incidence of proteorhodopsin genes in the ultraoligotrophic Eastern Mediterranean Sea. (1st March 2017) - Dubinsky, Vadim; Haber, Markus; Burgsdorf, Ilia; Saurav, Kumar; Lehahn, Yoav; Malik, Assaf; Sher, Daniel; Aharonovich, Dikla; Steindler, Laura
Summary: Sunlight can be directly harvested by photoheterotrophic bacteria to create a pH gradient across the membrane, which can then be utilized to produce ATP. Despite the potential importance of this trophic strategy, when and where such organisms are found in the seas and oceans is poorly described. Here, we describe the abundance and taxonomy of bacteria with different trophic strategies (heterotrophs, phototrophs and photoheterotrophs) in contrasting water masses of the ultra‐oligotrophic eastern Mediterranean Sea. These water bodies, an anticyclonic eddy and a high‐chlorophyll patch resulting from transport of nutrient‐rich coastal waters into offshore oligotrophic waters, each supported different microbial populations in surface waters. Based on infrared microscopy and metagenomics, aerobic anoxygenic photoheterotrophic (AAP) bacteria represented up to 10.4% of the microbial community. In contrast, the proteorhodopsin (PR) gene was found in 78.6%–118.8% of the bacterial genome equivalents, the highest abundance reported to date. These results suggest that PR‐mediated photoheterotrophy may be especially important in oligotrophic, potentially phosphate‐limited conditions.